Bahaya Guru-Guru Palsu (Teologi Surat 2 Petrus) dan Kontekstualisasi Pada Pendidikan Kristen di Indonesia - Jehezkiel Fransiscus Hanno VDK (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2022)
This research aims to see how dangerous false teachers are according to 2 Peter, and of course what they do and teach to many people, so that in the end they get lost and no longer live in the truth. From the existence of these false teachers, the world of today's Christian Education needs to learn to understand what things should not be taught and for educators, it is important to teach good things and behave in the truth, because they become role models for everyone, especially for the students. The method used in this study is a non-experimental qualitative. Researchers used exploratory literature research in the form of biblical theological research. This research consists of background problems, research methods, research results, discussion, and conclusions. This research shows how important the role of teachers is in the development of Christian Education. Seeing the dangers of false teachers and what they teach is a warning to the world of Christian Education in Indonesia. The existence and dangers of false teachers make the quality of teachers and their teachings must be given more attention and optimally improved so that they conform to the truth of God's word and produce successful Christian Education